2003
DOI: 10.1136/bmj.327.7412.426
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual function problems and help seeking behaviour in Britain: national probability sample survey

Abstract: Although similar findings have been reported in men who report same sex behaviour, 21 to our knowledge no other population study has focused specifically on sexual problems in bisexual as distinct from homosexual men.We thank Josephine Woolf for her collaboration in obtaining funding; Alice Gladwin, Monique Cloherty, and Üta Drescher for their assistance in collecting the data; and Bob Blizard for his statistical advice on the project. Contributors: See bmj.com Funding: health service research project grant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
248
2
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(285 citation statements)
references
References 4 publications
23
248
2
12
Order By: Relevance
“…A study in Britain found 53.8% of women had a minimum of one sexual problem lasting at least 1 month over a 2-year period. 14 The most widely cited study is based on the US National Health and Social Life Survey of 1992. This was published in 1999 and evaluated a National Probability Sample of 1749 women and 1410 men, aged 18-59 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Britain found 53.8% of women had a minimum of one sexual problem lasting at least 1 month over a 2-year period. 14 The most widely cited study is based on the US National Health and Social Life Survey of 1992. This was published in 1999 and evaluated a National Probability Sample of 1749 women and 1410 men, aged 18-59 years.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, scores o3.9 in all six domains were considered as sexual dysfunction. We further categorized female sexual function as four groups: normal female sexual function (total score X23), mild FSD (total score 18-23), moderate FSD (total score [11][12][13][14][15][16][17], and severe FSD (total scorep10).…”
Section: Methodsmentioning
confidence: 99%
“…Roughly 6% of men and 16% of women reported at least one persistent i sexual function problem in a recent national survey (Mercer et al, 2003). And in a recent study of General Practitioner (GP) attendees, 22% of men and 40% of women received at least one ICD…”
Section: Introductionmentioning
confidence: 99%
“…For example, over 50% of women in the UK report at least one sexual problem lasting a month or more during the previous year (Mercer et al 2003), and around a quarter have never or rarely achieved orgasm during the previous three months (Dunn et al 2002). There is controversy over whether the problem has a real medical basis, or whether it has partly been created by the media, pharmaceutical advertising and cultural expectations (Moynihan 2003).…”
Section: Introductionmentioning
confidence: 99%